The 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study: methods A visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993: métodos - Cora Luiza Araújo; Ana M. B. Menezes; Maria de Fátima A. Vieira; Marilda B. Neutzling; Helen Gonçalves; Luciana Anselmi; Samuel C. Dumith; Pedro C. Hallal (Cadernos de Saúde Pública, 2010)
The aim of this study is to describe the methodology of the 2004-2005 follow-up visit of the 1993 Pelotas (Brazil) birth cohort. All children born in Pelotas in 1993 and whose mothers lived in the city at that time were eligible to be enrolled in a longitudinal study. Between July 2004 and March 2005, all cohort participants were sought for a follow-up visit. Several strategies were used to help trace cohort members, including a census of the city's schools and a census of all households in the municipality. The Mortality Information System was monitored in order to identify deaths among cohort members. Of the 5,249 cohort members, 4,452 were interviewed in 2004-5. When added to the 141 deaths, these represent 87.5% of the original cohort. In spite of the logistic and financial difficulties, it is possible to carry out prospective studies with long-term follow-up in the Brazilian context. O objetivo deste artigo é descrever a metodologia do acompanhamento realizado em 2004-2005 da coorte de nascidos em 1993 na cidade de Pelotas, Rio Grande do Sul, Brasil. Todas as crianças nascidas em 1993 nessa cidade, cujas mães residiam no município, foram elegíveis para um estudo longitudinal. Entre os meses de julho de 2004 e março de 2005, todos os participantes da coorte foram procurados para um acompanhamento. Diversas estratégias de busca foram utilizadas para auxiliar na localização dos participantes, sendo as principais um censo em todas as escolas do município e um censo domiciliar. O Sistema de Informações sobre Mortalidade foi monitorado para detecção de óbitos de participantes da coorte. Dos 5.249 participantes da coorte, 4.452 foram entrevistados em 2004-2005, os quais, somados aos 141 óbitos detectados, representam 87,5% da coorte original. Apesar das dificuldades logísticas e financeiras, é possível realizar estudos prospectivos com altas taxas de acompanhamento em longo prazo no contexto brasileiro.